1997
DOI: 10.1021/jp970308l
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Trapping of Photoinjected Excess Electrons in Double-Stranded B-Form DNA But Not in Single-Stranded DNA

Abstract: Photoexcitation of a pyrene derivative covalently bound to double-stranded calf thymus DNA with 355 nm Nd:YAG laser pulses (fwhm ) 24 ps, 50 mJ/cm 2 /pulse) results in the efficient two-photon-induced ionization of the pyrenyl residues. By use of nanosecond transient absorption techniques, it is shown that the excess electrons injected into the DNA can reduce methylviologen cations (MV 2+ ) that are noncovalently bound to the DNA but not MV 2+ in the outer aqueous solution phase. In double-stranded DNA, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The photoirradiation of 5‘-Py-A with a 355-nm laser pulse (fwhm = 4 ns, 20 mJ/pulse) under Ar-purged conditions lead to the formation of absorption bands at 470 and 630 nm immediately after the flash. These two absorption bands were assigned to Py •+ and a solvated electron (e aq - ), respectively, demonstrating the successful electron ejection from Py to the solvent water during the excitation . The transient absorption of e aq - decayed in about 1 μs under Ar, and it decayed within a laser pulse duration under N 2 O-saturated condition (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…The photoirradiation of 5‘-Py-A with a 355-nm laser pulse (fwhm = 4 ns, 20 mJ/pulse) under Ar-purged conditions lead to the formation of absorption bands at 470 and 630 nm immediately after the flash. These two absorption bands were assigned to Py •+ and a solvated electron (e aq - ), respectively, demonstrating the successful electron ejection from Py to the solvent water during the excitation . The transient absorption of e aq - decayed in about 1 μs under Ar, and it decayed within a laser pulse duration under N 2 O-saturated condition (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…They showed that the photoinduced electron transport from an intercalated Ru(II) complex to an intercalating Rh(III) electron acceptor proceeds rapidly over 40 A ˚.67 Four years later, Shafirovich's group published a nanosecond time-resolved study of electron injection into DNA by a benz[a]pyrene-guanosine adduct and electron trapping by non-covalently bound methyl viologen (Mv). 328 Since the electron trapping in this assay did not occur site-selectively the results in terms of sequence and distance dependence of electron transport are rather difficult to interpret.…”
Section: Spectroscopic Investigation Of Reductive Electron Transfer I...mentioning
confidence: 94%
“…The dynamics of charge injection and migration over relatively short distances has been investigated by means of transient absorption spectroscopy on femtosecond-to-microsecond time scales. Most of the information obtained to date pertains to hole injection (oxidation of nucleobases). Current knowledge of photoinduced electron injection (reduction of nucleobases) in systems with known donor−acceptor distances is limited to preliminary studies of the efficiency of T−T dimer repair via electron injection from a flavin nucleobase and the picosecond dynamics of electron injection to neighboring T or C bases from singlet donors. ,, We report here the picosecond dynamics of electron injection in synthetic DNA hairpins from a stilbenediether singlet ( 1 Sd*) electron donor to four different neighboring base pairs which function as electron acceptors and the distance dependence of electron injection from 1 Sd* to thymine when the donor and acceptor are separated by a variable number of noncanonical G:G base pairs (Figure ) 1 Structures of synthetic DNA hairpins and the stilbenediether linker Sd . …”
mentioning
confidence: 99%